"Global/local" community engagement: advancing integrative learning and situated solidarity. Issue 1 (2nd January 2018) - Houston, Serin D.; Lange, Kirk
Abstract: This article illustrates how "global/local" community engagement, a particular form of experiential learning and political work that draws upon geography conceptually, pedagogically, and programmatically, is well suited to advance integrative learning and invite students into social action. Through specific examples from Mount Holyoke College, we argue that "global/local" community engagement helps students cultivate the skills and dispositions of reciprocity, reflexivity, and place-based and interdependent knowledge production. These are habits of mind and patterns of praxis necessary for enacting "situated solidarity, " a practice with great potential for grappling with the complex challenges and marked divisiveness of the twenty-first century. As our empirical examples demonstrate, the geographic concept of contour lines matched with the pedagogies of accompaniment and co-labor guide "global/local" community engagement. We conclude with a set of recommendations for implementing "global/local" community engagement in other institutions of higher education to reveal the context-specificity of our examples and the possibilities for application elsewhere.